Evaluasi Mutu dan Kemurnian Madu Tawon yang Beredar di Kota Semarang - Ch Retnaningsih; Vera Handayani; Lucia Sri Lestari (agriTECH, 2005)
Honey is a thick liquid that are collected, moded and condensed by honey bees from the nectar source. Along with its fame, honey that are distributed now a days appear in different kind of quality and variety. The aim of the study was to determine the quality of commercial honeys distributed in Semarang and compared with fresh honey. Samples of honey covered 6 brands of commercial honey and 3 brands of honey of "jamu" products. Commercial honeys were classified based on the price, i.e. those with the price of Rp. 3000-4000/100m1 and those with the price of Rp.5000-6000/10Orn1. The chemical analyses which had been done covered diastase's activity, hidroxymethylfurfural (HMF), reducing sugar, sucrose and moisture. The results showed that honey composition were influenced by the nectar source, age of the honey bees and also the environment of nectar source. The decrease of honey's quality was influenced by the invertase enzyme, also the condition and method to preserve honey during storage. According to the result of the quality and authenticity, honeys from Vamu" product fulfilled the quality standard of SNI-3545-1994, except for SM brand, containing reducing sugar and HMF lower than the SN1 standard. But if it was compared to commercial honeys and fresh honey the quality was much lower. The result showed that honey with the price of Rp.5000-6000/100m1 the quality wasn't assured to be better than those honey with the price Rp. 3000-4000/100m1. The result also showed the indication of high fructose corn syrup addition to honey.